Influence of the domicile on healthy behaviors of pregnant women - Adamczyk, Jakub Grzegorz; Turska, Anna; Boguszewski, Dariusz (Polish Journal of Public Health, 2012)
Introduction. The motor activity, eating habits, preventive behaviors, psychological attitude, or health practice can have a fundamental influence on pregnancy and childbirth.Aim. Presenting and comparing healthy behaviors of pregnant women living in the area of big city and small town.Material and methods. The examined group covered 171 women after childbirth staying at the labor ward. The examination was conducted on the second or third day after the childbirth, with the use of the author’s questionnaire including 37 questions.Results. The attitudes of pregnant women were health promoting. The pregnancy induced women to take up new or continue healthy behaviors. An essential relationship was confirmed between the physical activity during pregnancy and the mood as well as physical fitness after childbirth.Conclusions. In the face of the achieved results, special attention should be paid to the promotion of healthier lifestyle of pregnant women; especially to various forms of the motor activity.